2012
DOI: 10.21608/jpp.2012.84192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integration Between Compost and Urea Fertilizer on the Productivity of Sakha 105 Rice Cultivar

Abstract: Field experiments were conducted at Rice Research and Training Center, Sakha, Kafrelseikh Governorate, Egypt during two summer seasons 2010 and 2011 to study the influence of integration between compost and urea fertilizer on yield and its components of Sakha 105 rice cultivar as well as nitrogen uptake in rice grains and soil organic matter percentage. The treatments were (0, 5 ton compost/ ha, 165 kg N/ha, 5 ton compost + 55 kg N/ha and 5 ton compost + 110 kg N/ha). The results revealed that compost and mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…Surekha et al, (2006) reported that rice straw incorporation or organic manure application increased significantly NH4 concentration in rice soil. Similar trend was found by Naeem, (2012), andSelvarajh et al, (2021).…”
Section: Nutrients Availability In the Soil Available Ammonium (Ppm)supporting
confidence: 87%
See 1 more Smart Citation
“…Surekha et al, (2006) reported that rice straw incorporation or organic manure application increased significantly NH4 concentration in rice soil. Similar trend was found by Naeem, (2012), andSelvarajh et al, (2021).…”
Section: Nutrients Availability In the Soil Available Ammonium (Ppm)supporting
confidence: 87%
“…Rice straw contained less total N and higher C:N ratio than compost and farm yard manure (Table 3). Similar trends were obtained by Ahmed and Naeem (2012), Metwally (2015), Gharieb et al, (2016), Halder et al, (2020), Qaswar et al, (2020 and Sahu et al, (2020). Means of each factor designated by the same latter are not significantly different at 5% level using Duncan's Multiple Range Test.…”
Section: Grain Yield (T Ha -1 )supporting
confidence: 80%